From labor to finance: understanding the failure of socialist economic policies in Spain - Perez, Sofia A. (1999)
This article seeks to explain the Spanish Socialist Party's (PSOE's) failure to reverse Spain's dismal employment record during the course of its long government tenure from 1982 until 1996. Most efforts to explain Spain's position at the extreme of the unemployment spectrum in Europe follow the prevalent tendency in the comparative political economy literature by giving causal primacy to labor market institutions. This article challenges this labor-market-centered view by arguing that the failure of the Socialist government's economic policy strategy is to be found in the interaction of two other factors: the biased course of financial liberalization and the perverse effects of the PSOE's macroeconomic policy strategy on inflation and on the process of social concertation (national wage bargaining). The article also seeks to explain the PSOE's choices in these policy areas. - Reproduced
Keywords: Spain - Economic policy; Economic policy